(untitled) (Scottish Historical and Archaeological Internet Reports, 2009)
This chapter presents a physical description of the site, location, extent of erosion. method of access and details of previous work. The survey identified two buildings and a perimeter wall which also formed a small enclosed courtyard. A possible path led to the lower reaches of the stack. An isolated pit contained a large sherd of possible Neolithic pottery. It is possible that continued erosion will destroy the site within twenty years.